2018
DOI: 10.1007/s00382-018-4532-5
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric rivers impacting Northern California and their modulation by a variable climate

Abstract: Understanding the role of climate variability in modulating the behavior of land-falling atmospheric rivers (ARs) is important for seasonal and subseasonal predictability for water resource management and flood control. We examine daily activity of ARs targeting the Northern California coast over six decades using observations of synoptic-scale circulation, high-resolution precipitation, and a long-term AR detection catalog to quantify distinct types of land-falling ARs categorized by their circulation feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 32 publications
7
64
0
Order By: Relevance
“…We also note that statistical downscaling is an alternative approach for precipitation downscaling (Pierce et al, ). For example, Guirguis et al () recently assessed impacts of wetter/stronger ARs in a warming climate on fine‐resolution precipitation over Western North America using statistical (Localized Constructed Analogs) downscaling of precipitation.…”
Section: Methods and Modelingmentioning
confidence: 99%
“…We also note that statistical downscaling is an alternative approach for precipitation downscaling (Pierce et al, ). For example, Guirguis et al () recently assessed impacts of wetter/stronger ARs in a warming climate on fine‐resolution precipitation over Western North America using statistical (Localized Constructed Analogs) downscaling of precipitation.…”
Section: Methods and Modelingmentioning
confidence: 99%
“…ARs are also evident in a self-organizing map (SOM) analysis of moisture transport associated with extreme precipitation in the Intermountain West (Swales et al 2016). Analyses of the synoptic circulations associated with AR landfalls in Northern California further indicate that, although ENSO is not known to impact AR landfall frequencies in this region, it does impact AR orientations at landfall (Guirguis et al 2018b), promoting southerly (westerly) orientations during El Niño (La Niña) winters, which bolsters canonical ENSO precipitation anomalies in West Coast precipitation.…”
Section: Atmospheric Riversmentioning
confidence: 99%
“…3. Apply the Guan and Waliser (2015) AR detection algorithm, with the refinements in Guan et al (2018), to the IVT fields for each hindcast system, and for the contemporaneous reanalysis data set used to verify the hindcasts. AR objects are detected based on the seasonal 85th percentile threshold of IVT magnitude from the ERA-I data set at each grid cell and based on geometric constraints described in Guan and Waliser (2015).…”
Section: Hindcast Systems and Reanalysis Datamentioning
confidence: 99%
“…Atmospheric rivers (ARs) are elongated regions of intense horizontal water vapor transport, which are often associated with a baroclinic midlatitude cyclone (Neiman et al, ; Ralph et al, ; Ralph et al, ; Zhang et al, ; Zhu & Newell, ). Many studies have revealed the important link between ARs and annual precipitation over different regions around the globe (Dettinger et al, ; Lavers et al, ; Ralph & Dettinger ; Neiman et al, ; Lavers & Villarini, ; Lamjiri et al, ; and others), their association with global floods and water availability (Ralph et al, ; Leung & Qian, ; Ralph & Dettinger ; Paltan et al, ; Corringham, ), their relationship to snowpack over the western U.S. (Goldenson et al, ; Guan et al, ; Huning et al, , ), their importance to extratropical climate and hydrology (Gorodetskaya et al, ; Nash et al, ), and their projected changes in a warming climate (e.g., Espinoza et al, ; Guirguis et al, ). In addition, a new AR scale has recently been introduced which groups ARs into categories based on their intensity, duration, and beneficial or hazardous impacts on society (Ralph et al, ).…”
Section: Introductionmentioning
confidence: 99%